2020
DOI: 10.1186/s12864-020-07056-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis of root, stem, and leaf tissues of Entada phaseoloides reveals potential genes involved in triterpenoid saponin biosynthesis

Abstract: Background Entada phaseoloides (L.) Merr. is an important traditional medicinal plant. The stem of Entada phaseoloides is popularly used as traditional medicine because of its significance in dispelling wind and dampness and remarkable anti-inflammatory activities. Triterpenoid saponins are the major bioactive compounds of Entada phaseoloides. However, genomic or transcriptomic technologies have not been used to study the triterpenoid saponin biosynthetic pathway in this plant. Results We performed comparati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Even so, CYP736A (14 unigenes) and CYP734A1 (6 unigenes) showed significant up-regulation in the A stage compared to the C stage. UDP-glucosyltransferase is also considered a regulated factor in triterpenoid biosynthesis [11][12][13]. According to our analysis, related UGT unigenes were also identified including UDP-glucosyltransferase 73C (5 unigenes), UDP-glucosyltransferase 75B1 (2 unigenes), UDP-glucosyltransferase 73B2 (2 unigenes), cyanohydrin UDP-glucosyltransferase-UGT85K (3 unigenes), and UDP-glucosyltransferase 85A (1 unigenes).…”
Section: Rna-seq and Data Analysismentioning
confidence: 81%
See 3 more Smart Citations
“…Even so, CYP736A (14 unigenes) and CYP734A1 (6 unigenes) showed significant up-regulation in the A stage compared to the C stage. UDP-glucosyltransferase is also considered a regulated factor in triterpenoid biosynthesis [11][12][13]. According to our analysis, related UGT unigenes were also identified including UDP-glucosyltransferase 73C (5 unigenes), UDP-glucosyltransferase 75B1 (2 unigenes), UDP-glucosyltransferase 73B2 (2 unigenes), cyanohydrin UDP-glucosyltransferase-UGT85K (3 unigenes), and UDP-glucosyltransferase 85A (1 unigenes).…”
Section: Rna-seq and Data Analysismentioning
confidence: 81%
“…Kuntze, and Entada phaseoloides (L.) Merr. [11][12][13], and the structure gene expression patterns between species were different. Our research found triterpenoids content in old green leaves than red new leaves, and this was associated with the MVA (HMGS and HMGR) pathway instead of the MEP pathway.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Triterpene saponins are the primary biologically active compounds in E. phaseoloides. Liao et al (2020) conducted comparative transcriptome analysis of the root, stem, and leaf tissues of E. phaseoloides and identified 26 cytochrome P450 and 17 uridine diphosphate glycosyltransferase candidate genes related to triterpene saponin biosynthesis. The findings contributed to investigations on the functional genomics of triterpene saponin biosynthesis.…”
Section: Exploring the Biosynthetic Pathways Of Secondary Metabolitesmentioning
confidence: 99%